PENDAMPINGAN PEMBUATAN ECOBRICK UPAYA MENUMBUHKAN SEKOLAH RAMAH LINGKUNGAN DI SMPN 1 RANTAU PANDAN - Zahara Puan Budi Putri, Neysha; Fitriani, Yessy (Jurnal Pengabdian Pendidikan Masyarakat (JPPM), 2025)
Plastic waste is in increasing, this due to the widespread use of plastic packaging for food, In School such as canteen and garden are be plastic dominant and environment pollution. Making Ecobricks can be an effective effort in creating environmentally friendly schools. Ecobricks are building materials made from used plastic bottles filled with non-organic plastic waste to produce a strong and durable material. By using ecobricks, we can reduce plastic waste that pollutes the environment, while turning it into useful materials. By involving all elements of the school and community, making ecobricks will not only reduce plastic waste, but also support the construction of schools that are more environmentally friendly and sustainable. It can also be an example for students to practice ecological awareness in everyday life. The service method used is the method of providing assistance to SMPN1 Rantau Pandan students through the use of recycling plastic drink bottle caps. Ecobricks are a simple solution for processing plastic waste so that it is useful for schools in maintaining environmentally friendly schools. Ecobricks have been proven effective in reducing plastic waste and creating encironmental health.